The Analysis Of The Relationship Between Inflation, Unemployment And Economic Growth In Nigeria (1980-2014). - Darma, Nazifi Abdullahi; Onimisi, Aliyu Musari (Archives of Business Research, 2017)
This research work investigates the relationship between inflation, unemployment and economic growth in Nigeria (1980-2014). The objectives of the study is to examine the short run and the long run relationship between inflation, unemployment and economic growth in Nigeria. It begins with the application of Augmented Dickey-Fuller techniques to examine the unit root property of the time series data after which Autoregressive Distributive Lag Model (ARDL) was used to determine the cointegration or long-run relationship. Lastly, Vector Autoregressive (VAR) model test was conducted to investigate the causal relationship between the variables studied. Empirical findings from ARDL model shows that there is no short and the long run relationship between unemployment rate, inflation rate and real GDP growth rate in Nigeria. The results of VAR model do not indicate robust evidence and do not confirm an inverse linkage between unemployment rate and economic growth. In view of the foregoing, the study therefore recommends the adoption of fiscal measures that enhance economic growth and private sector activities, hence promoting economic growth and employment generation. In addition, key economic incentives are needed towards attracting foreign direct investment (FDI) in productive sectors of the national economy and expanding resource utilization base.